Improving Hip Fracture Care in Ireland: A Preliminary Report of the Irish Hip Fracture Database. (8th December 2014) - Ellanti, Prasad; Cushen, Breda; Galbraith, Adam; Brent, Louise; Hurson, Conor; Ahern, Emer
Abstract : Introduction . Hip fractures are common injuries in the older persons, with significant associated morbidity and mortality. The Irish Hip Fracture Database (IHFD) was implemented to monitor standards of care against international standards. Methods . The IHFD is a clinically led web-based audit. We summarize the data collected on hip fractures from April 2012 to March 2013 from 8 centres. Results . There were 843 patients with the majority being (70%) female. The 80–89-year age group accounted for the majority of fractures (44%). Most (71%) sustained a fall at home. Intertrochanteric fractures (40%) were most common. Only 28% were admitted to an orthopaedic ward within 4 hours. The majority (97%) underwent surgery with 44% having surgery within 36 hours. Medical optimization (35%) and lack of theatre space (26%) accounted for most of the surgical delay. While 29% were discharged home, 33% were discharged to a nursing home or other long-stay facilities. There was a 4% in-hospital mortality rate. Conclusions . Several key areas in both the database and aspects of patient care needing improvement have been highlighted. The implementation of similar databases has led to improved hip fracture care in other countries and we believe this can be replicated in Ireland.